1991
DOI: 10.3109/08990229109144749
|View full text |Cite
|
Sign up to set email alerts
|

Response Properties of Periodontal Mechanosensitive Neurons in the Trigeminal Spinal Tract Nucleus of the Cat

Abstract: Periodontal mechanosensitive (PM) units were recorded from the trigeminal spinal tract nucleus (Vst) of the cat. The Vst is divided into three subnuclei: oralis (Vo), interpolaris (Vi), and caudalis (Vc). The receptive fields of PM units in Vo and Vi were arranged in a dorsoventral sequence in the mandibular to maxillary divisions, and those in Vc were arranged in a mediolateral sequence. The majority of Vo units were single-tooth ones, whereas more than half the Vi units and all the Vc ones were multitooth un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The present results have, however, shown that DL neurons respond to stimulation of low-threshold mechanoreceptors in the periodontal ligament, gingiva, or lip and to nociceptors in tooth pulp and/or tongue. This is consistent with findings that Vo receives inputs from low-or highthreshold mechanoreceptive afferent fibers innervating the oral cavity and perioral regions (Kruger and Michel, 1962a,b;Eisenman et al, 1963;Sessle and Greenwood, 1976;Hu et al, 1981Hu et al, , 1986Azerad et al, 1982;Shigenaga et al, 1986cShigenaga et al, , 1989bShigenaga et al, , 1990bTsuru et al, 1989;Dallel et al, 1990;Tabata and Karita, 1991;Takemura et al, 1991Takemura et al, , 1993Westberg and Olsson, 1991;Toda and Hayashi, 1992). Prior HRP tracing studies (Shigenaga et al, 1986a,b) have revealed that the dorsoventrally arranged topographic representation of the trigeminal dermatomes is clearly evident in the middle part of the ventral subnucleus of Vp, caudal part of the interpolar nucleus, and rostra1 part of the caudal nucleus, whereas the dorsomedial Vo receives overlapping projection from primary afferents innervating the oral cavity and perioral regions.…”
Section: Functional Properties Of Vo Neuronssupporting
confidence: 86%
See 1 more Smart Citation
“…The present results have, however, shown that DL neurons respond to stimulation of low-threshold mechanoreceptors in the periodontal ligament, gingiva, or lip and to nociceptors in tooth pulp and/or tongue. This is consistent with findings that Vo receives inputs from low-or highthreshold mechanoreceptive afferent fibers innervating the oral cavity and perioral regions (Kruger and Michel, 1962a,b;Eisenman et al, 1963;Sessle and Greenwood, 1976;Hu et al, 1981Hu et al, , 1986Azerad et al, 1982;Shigenaga et al, 1986cShigenaga et al, , 1989bShigenaga et al, , 1990bTsuru et al, 1989;Dallel et al, 1990;Tabata and Karita, 1991;Takemura et al, 1991Takemura et al, , 1993Westberg and Olsson, 1991;Toda and Hayashi, 1992). Prior HRP tracing studies (Shigenaga et al, 1986a,b) have revealed that the dorsoventrally arranged topographic representation of the trigeminal dermatomes is clearly evident in the middle part of the ventral subnucleus of Vp, caudal part of the interpolar nucleus, and rostra1 part of the caudal nucleus, whereas the dorsomedial Vo receives overlapping projection from primary afferents innervating the oral cavity and perioral regions.…”
Section: Functional Properties Of Vo Neuronssupporting
confidence: 86%
“…The dorsomedial subdivisions of Vo (V0.r and Vo.dm) have been reported to receive projections from primary afferents that innervate peri-and intraoral structures only (Arvidsson and Gobel, 1981;Marfurt, 1981;Westrum et al, 1981;Woda et al, 1983;Marfurt and Turner, 1984;Shigenaga et al, 1986bShigenaga et al, ,c, 1989aTsuru et al, 1989;Tabata and Karita, 1991;Takemura et al, 1991Takemura et al, , 1993 and to receive a disproportionately large representation of terminals from these afferents (see, e.g., Torvik, 1956;Shigenaga et al, 1986bShigenaga et al, , 1990b. It has recently been reported that Vo.r also receives collaterals from periodontal ligament afferents originating in the mesencephalic trigeminal nucleus (Shigenaga et al, 1989a).…”
mentioning
confidence: 99%
“…The present observation of the different degree of complexity (or simplicity) of synaptic connectivity between Vpv and Vo.r terminals raises a question as to whether such difference is related to morphological and functional distinctions between the two subnuclei. There is good evidence that input from SA receptors in periodontal ligament activates Vpv and Vo.r cells (Azerad et al, 1982;Dallel et al, 1990;Jacquin and Rhoades, 1990;Tabata and Karita, 1991). Most Vpv cells that are excited by SA periodontal afferent input send their axons into VPM (Azerad et al, 19821, but such cells are presumed to be very few in Vo.r because few labeled cells were observed by injecting HRP into the VPM (Burton and Craig, 1979;Fukushima and Kerr, 1979;Shigenaga et al, 1983;Yasui et al, 1983).…”
Section: Synaptic Organization Associated With Labeled Boutonsmentioning
confidence: 99%
“…The difference in projection sides between the cat and rat might be related to species differences and/or to specialization of mastication in each animal. [8,9], trigeminal sensory complex [23][24][25], thalamic VPM nucleus [3,14] and primary somatosensory cortex [26] in the cat (A) and rat (B). [8,9], trigeminal main sensory nucleus [23,25] and thalamic VPM nucleus [14,27] in the cat (A) and rat (B).…”
Section: Laterality Of the Rfsmentioning
confidence: 99%
“…3. Incidences of the single-tooth neurons in the trigeminal ganglion [8,9], trigeminal sensory complex [23][24][25], thalamic VPM nucleus [3,14] and primary somatosensory cortex [26] in the cat and rat. one tooth only, while the multitooth type refers to neurons that are sensitive to stimulation of plural teeth.…”
Section: Receptive Fields (Rfs)mentioning
confidence: 99%